An assessment of a bypassed area the case of Antique - Delgado, Carlo Balino
The issue of "bypassed areas in economic context seemed to "bypassed" in its very actual sense. This study primarily attempts: (1)to provide a celar description of bypassed area along with its causes and characteristics, and (2)to address the importance of such areas with respect to its economic development. However, this study was not limited to those aforementioned purposes, the researchers also used the concept of rural development as a strategy for overcoming bypassed area's problem since being bypassed tends to occur in an agrarian context and is essentially a rural phenomenon., Antique, an agricultural province located in Western Visayas, was chosen as an area subject to be evaluated whether it exhibits the characteristics as denoted by a bypassed area. This study makes use of secondary data which were mostly gathered from the Antique Provincial Planning and Development Office, National Statistical Coordination Board and national Statistics Office. These were essential in creating a picture of Antique's economy as placed against the conditions of a bypassed area and are also essential in the comparison to its fellow provinces in the region. It was observed in the study that Antique was predominantly rural in scope, thus, satisfying the primary premise of being a bypassed area that tends to occur in an agrarian context. Moreover, in aggregate, the province considerably exhibits several conditions that are perceived to be characteristics of a bypassed area. However, such state of being bypassed is by far critical in the real sense and is believed to be overcome depending upon the course of rural development in the province.